2021
DOI: 10.1038/s41392-021-00692-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a recombinant COVID-19 vaccine (Sf9 cells) in healthy population aged 18 years or older: two single-center, randomised, double-blind, placebo-controlled, phase 1 and phase 2 trials

Abstract: COVID-19 vaccines from multiple manufacturers are needed to cope with the problem of insufficient supply. We did two single-center, randomised, double-blind, placebo-controlled phase 1 and phase 2 trials to assess the safety, tolerability and immunogenicity of a recombinant COVID-19 vaccine (Sf9 cells) in healthy population aged 18 years or older in China. Eligible participants were enrolled, the ratio of candidate vaccine and placebo within each dose group was 3:1 (phase 1) or 5:1 (phase 2). From August 28, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…A variety of vaccines, including the mRNA and recombinant vaccines, were developed to prevent the spread of the disease. 1 , 2 There is an urgent need for testing the vaccine-induced long-term memory response based on the immunological principles and identifying the optimal combination of dose and injection manner to provide important information for clinical application.…”
mentioning
confidence: 99%
“…A variety of vaccines, including the mRNA and recombinant vaccines, were developed to prevent the spread of the disease. 1 , 2 There is an urgent need for testing the vaccine-induced long-term memory response based on the immunological principles and identifying the optimal combination of dose and injection manner to provide important information for clinical application.…”
mentioning
confidence: 99%
“…Then, the literature was screened by the following criteria: (1) healthy participants older than 16 years; (2) a sample size of at least 100 participants; (3) randomized controlled design; and (4) the most recent study phase. A total of 33 studies met the inclusion criteria [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], and we extracted the vaccine platform, name, location, age, study phase, sample size, and safety data (especially the neurological AEs) from the included clinical trials (Table 2 ). Moreover, it must be noted that vaccine-unrelated AEs as specified in the articles have been excluded.…”
Section: Systemic and Neurological Aes Following Vaccinationsmentioning
confidence: 99%
“…The risk of bias was analyzed using the RoB 2 tools for 61 trials included in this review. Among them, 12 clinical trials scored as "high-risk" [19,33,34,39,40,46,47,49,[53][54][55]77]; 28 trials categorized as trials with 'some concerns'; while the remaining trials (21 studies) were classified as "low-risk" (Figure 2). Four studies were identified with the most "highrisk" due to unconcealed intervention to the participants and outcome measure affected by the knowledge of investigators [46,47,54,55].…”
Section: Risk Of Biasmentioning
confidence: 99%
“…A total of 36 studies (59.02%) adhered with the CONSORT recommendation for reporting harms, with the two highest studies reporting 20 score of 21 THRS, as shown in Table 2. The most significant domain that induced the high-risk judgment was biased in measurement of the outcome (domain 4) [33,34,40,46,47,49,[53][54][55]. There were concerns that the clinical trial outcome would be affected by prior knowledge of the outcome assessor.…”
Section: Adherence To Consort Recommendationsmentioning
confidence: 99%